ANALISIS INOVASI, TEAM WORK DAN PENGARUHNYA TERHADAP KINERJA ORGANISASIONAL MELALUI PEMBELAJARAN ORGANISASIONAL PADA BATALION TANKFIB 1 MARINIR - Utomo, Joko (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
This research aims to analyze the influence of innovation and team work on organizational performance through organizational learning in the 1st Marine Tankfib Battalion. The population in this study were all 220 soldiers working in the 1st Marine Tankfib Battalion. This type of research is explanatory with a quantitative approach. The sampling technique used in this research was determined by 25 independent variables, so the total sample in this research was 75 respondents. The data analysis technique for this research uses SEM-PLS. The research results show that innovation has a significant effect on organizational performance, teamwork has a significant effect on organizational performance, organizational learning is proven to have an effect on organizational performance. The influence test did not show that innovation had a positive effect on organizational performance through organizational learning and teamwork had a positive effect on organizational performance through organizational learning.